2020
DOI: 10.1371/journal.pone.0239133
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety in young people: A prevalence study in seven countries

Abstract: Social anxiety is a fast-growing phenomenon which is thought to disproportionately affect young people. In this study, we explore the prevalence of social anxiety around the world using a self-report survey of 6,825 individuals (male = 3,342, female = 3,428, other = 55), aged 16-29 years (M = 22.84, SD = 3.97), from seven countries selected for their cultural and economic diversity: Brazil, China, Indonesia, Russia, Thailand, US, and Vietnam. The respondents completed the Social Interaction Anxiety Scale (SIAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 68 publications
3
97
1
14
Order By: Relevance
“…There is good evidence that individuals with subclinical social anxiety also experience functional impairment across several aspects of life and have an elevated risk of comorbid psychiatric disorders (Fehm et al, 2008;Filho et al, 2010;Crişan et al, 2016). In other words, the total number of individuals with social anxiety who experience stress and impairments likely exceeds the estimated prevalences of SAD (Jefferies and Ungar, 2020). Reflecting this issue, prevalence studies based on self-report questionnaires with diagnostic cutoffs tend to report higher prevalence rates (Inglés et al, 2010;Gren-Landell et al, 2011;Jefferies and Ungar, 2020) than studies based only on diagnostic interviews (Demir et al, 2013;Canals et al, 2019;Georgiades et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is good evidence that individuals with subclinical social anxiety also experience functional impairment across several aspects of life and have an elevated risk of comorbid psychiatric disorders (Fehm et al, 2008;Filho et al, 2010;Crişan et al, 2016). In other words, the total number of individuals with social anxiety who experience stress and impairments likely exceeds the estimated prevalences of SAD (Jefferies and Ungar, 2020). Reflecting this issue, prevalence studies based on self-report questionnaires with diagnostic cutoffs tend to report higher prevalence rates (Inglés et al, 2010;Gren-Landell et al, 2011;Jefferies and Ungar, 2020) than studies based only on diagnostic interviews (Demir et al, 2013;Canals et al, 2019;Georgiades et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the total number of individuals with social anxiety who experience stress and impairments likely exceeds the estimated prevalences of SAD (Jefferies and Ungar, 2020). Reflecting this issue, prevalence studies based on self-report questionnaires with diagnostic cutoffs tend to report higher prevalence rates (Inglés et al, 2010;Gren-Landell et al, 2011;Jefferies and Ungar, 2020) than studies based only on diagnostic interviews (Demir et al, 2013;Canals et al, 2019;Georgiades et al, 2019). Moreover, differences between interview-and self-report -based prevalence rates could be due to the nature of social anxiety itself, as fear of an interview situation may result in nonattendance or underreporting of symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study identified mismatches between the DSM criteria and the local phenomenology of SAD in specific cultural contexts [45]. Although there is mounting evidence [46][47][48] that the prevalence and expression of SAD are culture-dependent, most of the research on social anxiety has been conducted in the United States. Further, the SIAS and SPS scales have only been used in Australian, American, Japanese, and South Korean samples [29,49].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies showed the clinical utility of the scales [29,30], this has only been done on American samples. Since the prevalence and expression of SAD are culture-dependent [46][47][48], examining the clinical applicability of SIAS-6 and SPS-6 in other cultures is necessary. As social anxiety often develops during adolescence [53], apart from an adult and a clinical sample, we also recruited an adolescent community sample to evaluate whether the questionnaires are suitable for screening for SAD in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, aymat zibur has been put forward as a particular concern for orthodox Jews that translates as 'fear of the community' and relates to concerns about performing religious activities (Greenberg, Stravynski, & Bilu, 2004). These studies are part of an emerging body of literature suggesting that there may be culture-specific elements of social anxiety, including domains of concern and the situations that can prompt social anxiety (see also Jefferies & Ungar, 2020;Kleinknecht, Dinnel, Kleinknecht, Hiruma, & Harada, 1997).…”
Section: Introductionmentioning
confidence: 99%